Effect of age on upper and lower eyelid saccades - Leite,L.V.O. (2006)
To study the effect of age on the metrics of upper and lower eyelid saccades, eyelid movement of two groups of 30 subjects each were measured using computed image analysis. The patients were divided on the basis of age into a younger group (20-30 years) and an older group (60-91 years). Eyelid saccade functions were fitted by the damped harmonic oscillator model. Amplitude and peak velocity were used to compare the effect of age on the saccades of the upper and lower eyelid. There was no statistically significant difference in saccade amplitude between groups for the upper eyelid (mean ± SEM; upward, young = 9.18 ± 0.32 mm, older = 8.93 ± 0.31 mm, t = 0.56, P = 0.58; downward, young = 9.11 ± 0.27 mm, older = 8.86 ± 0.32 mm, t = 0.58, P = 0.56) However, there was a clear decline in the peak velocity of the upper eyelid saccades of older subjects (upward, young = 59.06 ± 2.34 mm/s, older = 50.12 ± 1.95 mm/s, t = 2.93, P = 0.005; downward, young = 71.78 ± 1.78 mm/s, older = 60.29 ± 2.62 mm/s, t = 3.63, P = 0.0006). In contrast, for the lower eyelid there was a clear increase of saccade amplitude in the elderly group (upward, young = 2.27 ± 0.09 mm, older = 2.98 ± 0.15 mm, t = 4.33, P < 0.0001; downward, young = 2.21 ± 0.10 mm, older = 2.96 ± 0.17 mm, t = 3.85, P < 0.001). These data suggest that the aging process affects the metrics of the lid saccades in a different manner according to the eyelid. In the upper eyelid the lower tension exerted by a weak aponeurosis is reflected only on the peak velocity of the saccades. In the lower eyelid, age is accompanied by an increase in saccade amplitude which indicates that the force transmission to the lid is not affected in the elderly.